The Business Owners SMES Sector of Intention to Use The Sevices By External Accountants - Irwansyah Irwansyah; Madani Hatta; Ghulam Ferdi Al Masriki (JAFFA, 2018)
This study aimed to prove attitude toward behavior, subjective norm, perceived behavioral control, perception of the business owners SMEs sector about competence of the accountant external, size of business, and competitive industries has positive effect on the intention to use the services from external accountants. Respondents in this study were 67 business owners in SMEs sector in Bengkulu city. The method of collecting data in this study using a survey by questionnaires to the respondents either directly. The data was analyzed by using SmartPLS 3.0. The result show that attitude toward behavior, subjective norm, perceived behavioral control, external accountant to be competent, size of business, and competitive industries has positive effect on intention to use the services from external accountants.